KAJIAN YURIDIS TERHADAP SYARAT SAH DAN UNSUR-UNSUR DALAM SUATU PERJANJIAN - M Zen Abdullah (Jurnal LEX SPECIALIS, 2010)
Agreement between one person and another person is a common thing lately, not economic aspect that agreement is also include social and cultural aspect, but so many people doesnt understand about the meaning of element in agreement it caused some people dont give more attention to that aspect althoght it was an importance element, because so many agreement hs been ended to the court caused by inperfection element so one person feel his right was violated and another person have the same feelling to, so this journal try to descibe about the condition and element that must be include in every good agreement. Key Note : Condition and element in good agreement